A poética de Kokin Wakashü (Estudos Japoneses, 1997)
Translation of the Kokin wakashü preface’s, written by its organizer KinoTsurayuki in which he exposes a briefing of Japanese aristocratic poetics in early Xth century, followed by a short analysis.